Synthesizing and Evaluating the Photocatalytic and Antibacterial Ability of TiO2/SiO2 Nanocomposite for Silicate Coating - Le, Manh-Cuong; Le, Thu-Huong; Bui Thi, Thanh-Huyen; Nguyen, Quang-Dat; Do Thi, Thanh-Ha; Tran Thi, Minh-Nguyet (Frontiers in Chemistry, 2021)
The TiO2/SiO2 nanocomposite has been synthesized by a sol-gel method and investigated the effect of the SiO2 content (0, 5, 10, 15, 20, and 50%) on the rutile-to-anatase phase transition of TiO2 NPs. In order to increase the photocatalytic efficiency of the nanocomposite and decrease the price of material, the TiO2/SiO2 Nc with content SiO2 of 15% sample is chosen for preparing silicate coating. The efficiency of photocatalytic MB and antibacterial ability in the air of W silicate coating (adding TiO2/SiO2 Nc (15%)) achieve almost 100% for 60 h and 94.35% for 3 h, respectively. While the efficiency of photocatalytic MB and antibacterial ability of WO silicate coating (adding commercial TiO2/SiO2) is about 25–30% for 60 h and 6.02% for 3 h, respectively. The presence of TiO2/SiO2 Nc (15%) with a larger surface area in W silicate coating can provide increased centers for absorption, photocatalytic reaction, and the contact between sample and bacteria lead to enhance the photocatalytic and antibacterial ability of W silicate coating.